Oxidação úmida de fenóis com catalisadores de ferro suportado em argilominerais em reator de leito de lama (slurry) - Santiago Júnior, Aristides Felipe (2010)
The wet oxidation of organic compounds with CO2 and H2O has been demonstrated to be an efficient technique for effluent treatment. This work focuses on the synthesis, characterization and catalytic performance of Fe-MnO2/CeO2, K-MnO2/CeO2/ palygorskite and Fe/ palygorskite toward the wet oxidative degradation of phenol. The experiments were conducted in a sludge bed reactor with controlled temperature, pressure and stirring speed and sampling of the liquid phase. Experiments were performed on the following operating conditions: temperature 130 ° C, pressure 20.4 atm, catalyst mass concentration of 5 g / L initial concentration of phenol and 0.5 g / L. The catalytic tests were performed in a slurry agitated reactor provided with temperature, pressure and agitation control and reactor liquid sampling. The influences of iron loaded on the support (0.3; 7 and 10%, m/m) and the initial pH of the reactant medium (3.1; 6.8; 8.7) were studied. The iron dispersion on the palygorskite, the phase purity and the elemental composition of the catalyst were evaluated by X-Ray Difraction (XRD), Scanning Electron Microscopy (SEM) and X-Ray Flourescence (XRF). The use of palygorskite as support to increase the surface area was confirmed by the B.E.T. surface results. The phenol degradation curves showed that the Fe3+ over palygorskite when compared with the other materials tested has the best performance toward the (Total Organic carbonic) TOC conversion. The decrease in alkalinity of the reaction medium also favors the conversion of TOC. The maximum conversion obtained from the TOC with the catalyst 3% Fe / palygorskite was around 95% for a reaction time of 60 minutes, while reducing the formation of acids, especially acetic acid. With products obtained from wet oxidation of phenol, hydroquinone, p-benzoquinone, catechol and oxalic acid, identified and quantified by High Performance Liquid Chromatography was possible to propose a reaction mechanism of the process where the phenol is transformed into the homogeneous and heterogeneous phase in the other by applying a kinetic model, Langmuir-Hinshelwood type, with evaluation of kinetic constants of different reactions involved.